PANDALUYU VILLAGE, KP. PAKALONGAN, POST-EARTHQUAKE DISASTER VICTIM’S ENTREPRENEURSHIP SUPPORT - Muniroh, Leny; Ritzkal, Ritzkal; Parinduri, Siti Khodijah (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
The initial observation showed that there were 27 RTs spread across Padaluyu Village. 8 RTs suffered very severe damage (all houses collapsed) 19 RTs suffered severe and moderate damage. The earthquake in Cianjur was considered quite devastating because with a magnitude of 5.6 SR, it caused severe damage and even caused many casualties who are still missing because they were buried by the ruins of the building. The objectives of this activity are: 1. Supporting communities for economic recovery through entrepreneurial motivation & mentoring. 2. Building villages that have been affected by the earthquake disaster to get back on their feet carried out by lecturers and students with cross-disciplinary knowledge. 3. Socialization and education on how to maintain personal hygiene and the post environment aims to minimize the accumulation of garbage. The method used is starting from Mapping and Coordination of Local Officials, Community Needs, Program Coordination with Partners, Activity Preparation and Facilitators, Entrepreneurship Motivation, Training on Recycling goods into economic goods. The result of this activity is that sustainable innovation is expected to increase the capacity of residents in realizing the marketing of these pillows.